Preparation of Primary Mixed Glial Cell Cultures from Adult Mouse Spinal Cord Tissue. Issue 4 (12th April 2023) - Cao, Ling; Bean, Elizabeth N.; Malon, Jennifer T.
Abstract: Central nervous system glial cells are known to mediate many neurocognitive/neurodegenerative diseases, including Alzheimer's and Parkinson's diseases. Similar glial responses have been recognized as critical factors contributing to the development of diseases in the peripheral nervous system, including various types of peripheral neuropathies, such as peripheral nerve injury‐induced neuropathic pain, diabetic neuropathy, and HIV‐associated sensory neuropathy. Investigation of the central mechanisms of these peripherally‐manifested diseases often requires the examination of spinal cord glial cells at cellular/molecular levels in vitro. When using rodent models to study these diseases, many investigators have chosen to use neonatal cerebral cortices to prepare glial cultures or immortalized cell lines in order to obtain sufficient numbers of cells for assessment. However, differences in responses between cell lines versus primary cultures, neonatal vs. adult cells, and brain vs. spinal cord cells may result in misleading data. Here, we describe a protocol for preparing mixed glial cells from adult mouse spinal cord that can be used for direct in vitro evaluations or further preparation of microglia‐enriched and microglia‐depleted cells. In this protocol, spinal cord tissue is enzymatically dissociated and adult mixed glial cells are ready to be used between 12 and 14 days after the establishment of the culture. This protocol may be further refined to prepare spinal cord glial cells from spinal cord tissues of adult rats and potentially other species. Mixed glial cultures can be prepared from animals of different strains or post‐in vivo manipulations and therefore are suitable for studying a variety of diseases/disorders that involve spinal cord pathological changes, such as amyotrophic lateral sclerosis and multiple sclerosis, as well as toxin‐induced changes. © 2023 Wiley Periodicals LLC. Basic Protocol : Preparation of primary mixed glial cell cultures from adult mouse spinal cord tissue